Tarik Menarik Kewenangan Pemerintah Pusat dan Pemerintah Daerah dalam Penanganan Pandemi Covid-19 - Siti Chadijah; Asip Suyadi; Tohadi Tohadi (Program Studi Hukum Universitas Pamulang, 2020)
The purpose of this study is to provide an evaluation of government policies that are expected to provide a clear picture or response of the diversity of central and regional policies in overcoming Covid-19. This study uses a normative legal research method with a statutory approach. The results of the study indicate that the Covid-19 case is a pandemic so it is stated that public health events are extra ordinary, causing health hazards across regions or countries. Thus, it has fulfilled the elements of public health emergencies so that the provisions that apply are referring to Law Number 6 Year 2018 on Health Quarantine.